2019
DOI: 10.1108/tqm-07-2018-0102
|View full text |Cite
|
Sign up to set email alerts
|

An empirical framework for soft CSFs of TQM in Chinese manufacturing companies

Abstract: Purpose The purpose of this paper is to frame an empirical model with the priority of implementing soft critical successful factors (CSFs) of total quality management (TQM) in Chinese manufacturing companies. Design/methodology/approach In total, 23 hypotheses regarding the relationships among TQM factors and business results have been developed through literature review and are tested using the structural equation modelling (SEM). The data used in this study are collected from 228 manufacturing companies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…The study has examined comprehensive testing of quality management practices as mediating variables. Generally, the findings of this study give credence to the expectation of Sadikoglu andOlcay (2014), andYan et al (2019), who believed that the absence of direct effects from QM to performance dimensions did not necessarily mean the absence of significant relationships, rather it only presented the possibility of indirect relationships through certain QM practices. The results of this study amplify the relevance of the theory of TQM 33,6 profound knowledge which posits the relevance of approaching management as a wholesome system and amplifies the importance of knowledge to the competitiveness of any firm.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The study has examined comprehensive testing of quality management practices as mediating variables. Generally, the findings of this study give credence to the expectation of Sadikoglu andOlcay (2014), andYan et al (2019), who believed that the absence of direct effects from QM to performance dimensions did not necessarily mean the absence of significant relationships, rather it only presented the possibility of indirect relationships through certain QM practices. The results of this study amplify the relevance of the theory of TQM 33,6 profound knowledge which posits the relevance of approaching management as a wholesome system and amplifies the importance of knowledge to the competitiveness of any firm.…”
Section: Discussionsupporting
confidence: 76%
“…The results of this study further expand researchers' understanding of employee focus practice as it builds on existing conflicting results. Bakotic and Rogosic (2015) found a significant direct relationship between employee focus and performance dimensions; however, Yan et al (2019) found no direct relationship and hinted at a possible mediating role. The results establish employee focus as a very good mediating variable between QM practices and performance dimensions.…”
Section: Hypotheses Testing Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this sense, the dynamics of microenterprises represent an important engine in the economic development of the region, especially in transition economies (Obi et al , 2018). Therefore, the use and application of SP plays a fundamental role in achieving the success of micro, small and medium enterprises (Alharbi et al , 2019; Barron and Chou, 2017; Jaafreh and Al-abedallat, 2013; Kitsios et al , 2019; Sainis et al , 2019; Yan et al , 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The "soft" or more qualitative aspects consist of people-related practices, a facet gaining momentum in contemporary research (Ooi et al, 2007). It is rationalised that soft practices produce a conducive work environment where hard practices can be implemented (Flynn et al, 1995;Yan et al, 2019). In a similar vein, the performance impacts of TQM also can be conceived on "soft" and "hard" platforms.…”
Section: Introductionmentioning
confidence: 99%